ANALISIS WAKTU DAN BIAYA MENGGUNAKAN METODE TIME COST TRADE OFF PADA PROYEK RUMAH TINGGAL 2 LANTAI: Time And Cost Analysis Using The Method Time Cost Trade Off In 2 Story Residential House Projects - Nakti, I Putu Yogistha; Dharma S., Bagus Widhi; Dewi, Baiq Reni Sari (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
The purpose of this study was to analyze time and costs with an initial Time Schedule using the Time Cost Trade Off method in a 2-storey Residential House Development Project. The method used to complete this research is descriptive method by examining case studies. The results showed that the addition of overtime hours had an optimum duration of 146 HK or 3% which resulted in an increase in project costs due to overtime hours of Rp. 2,628,281.25 so that the project cost increases from Rp. 767,230,000.00 to Rp. 769,858,281.25 Meanwhile, the addition of the number of workers with an optimum time of 146 HK resulted in an increase in project costs of IDR 95,000.00 so that the project cost increased from IDR. 767,230,000.00 to Rp. 76.325,000.00 . From the results of this study it can be seen that adding workers is more efficient than adding overtime hours with greater cost advantages.